Republic of Mozambique : Report on the Observance of Standards and Codes-Data Module; Update. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents an Update to the Data Module of the Report on the Observance of Standards and Codes (ROSC) for Mozambique. Despite the improvements in recent years, limitations in the coverage of most core comprehensive frameworks and indicators recommended in the General Data Dissemination System (GDDS) still exist, including the absence of a manufacturing or industrial production index and labor market indicators. In addition, data on public and publicly guaranteed external debt are not disseminated with the recommended breakdown. However, most GDDS recommendations regarding periodicity and timeliness have been met.